(untitled) (Journal of Universal Science Research, 2025)
The phenomenon of eponymy, where a word or phrase is derived from a proper noun, plays a significant role in shaping language and popular culture. This article explores the concept of eponyms, particularly in the context of the film industry, and how iconic characters, situations, or concepts from movies become integrated into the English language. By analyzing various examples of eponyms from films, we demonstrate how these terms transcend their cinematic origins and influence society’s understanding of specific traits, behaviors, and concepts.